2022
DOI: 10.22541/au.165899173.31165984/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are there differences in cardiothoracic surgery performed by trainees vs fully trained surgeons?

Abstract: Objectives: We sought to assess the safety of training in cardiothoracic surgery comparing outcomes of cases performed by trainees versus fully trained surgeons. Methods: EmBase, Scopus, PubMed, and OVID MEDLINE were searched in August 2021 independently by two authors. A third author arbitrated decisions to resolve disagreements. Inclusion criteria were articles on cardiothoracic surgery reporting on outcomes for trainees. Studies were assessed for appropriateness as per CBEM criteria. 892 results were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, surgeons should not be discouraged to let trainee operate first‐hand also on high‐risk profile patients. There are previous reports that focused on this issue and showed that regardless of the increased risk of nowadays patients trainee cases have similar favorable outcome than when performed by trainers and patients welfare is still preserved and prioritized 1,6,7 . Extension of training to complex operations also facilitates the always challenging transition from trainee to consultant position.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, surgeons should not be discouraged to let trainee operate first‐hand also on high‐risk profile patients. There are previous reports that focused on this issue and showed that regardless of the increased risk of nowadays patients trainee cases have similar favorable outcome than when performed by trainers and patients welfare is still preserved and prioritized 1,6,7 . Extension of training to complex operations also facilitates the always challenging transition from trainee to consultant position.…”
mentioning
confidence: 99%
“…Being able to perform surgery first‐hand represents the backbone of every training program and the key to successful development of the new generation of skilful surgeons. In this issue of the Journal, Comanici et al presented a thorough systematic summary of the current evidence on the outcomes of cardiothoracic operations performed by trainees 1 …”
mentioning
confidence: 99%
“…There are previous reports that focused on this issue and showed that regardless of the increased risk of nowadays patients trainee cases have similar favourable outcome than when performed by trainers and patients welfare is still preserved and prioritized. 1,6,7 Extension of training to complex operations also facilitates the always challenging transition from trainee to consultant position.…”
mentioning
confidence: 99%